Early-diverging bumblebees from across the roof of the world: the high-mountain subgenus Mendacibombus revised from species’ gene coalescents and morphology (Hymenoptera, Apidae) - Williams, Paul H.; Huang, Jiaxing; Rasmont, Pierre; An, Jiandong (Zootaxa, 2016)
The bumblebees of the subgenus Mendacibombus of the genus Bombus are the sister group to all other extant bumblebees and are unusual among bees for specialising in some of the highest elevation habitats with entomophilous plants on Earth. Most named taxa in this group (24 available names, from a total of 49 published names) were described originally from small differences in the colour pattern of the hair, many as parts (e.g. subspecies) of just one species. Subsequent taxonomic treatments recognised multiple species, but have described very few morphological characters, most of which are in the male genitalia. We examined 4413 specimens representing all of the named taxa from throughout the group’s global range to describe variation in DNA, in skeletal morphology, and in the colour patterns of the hair. Using Bayesian inference of the phylogeny from an evolutionary model for the fast-evolving COI gene, and fitting either general mixed Yule/coalescent models or Poisson tree process models, we identify COI gene coalescents, which are expected to characterise species as evolutionarily independent lineages. None of the conditions most likely to compromise this interpretation (biased sampling, paralogy, introgression, heteroplasmy, incomplete lineage sorting) appears to be a substantial problem in this case. In an integrative analysis, we show that colour patterns are often variable within these groups and do not diagnose the same groups as we recognise from genes; in contrast, the groups recognised from gene coalescents can also be diagnosed from differences we identify in morphology. We infer that the 12 groups with coalescents in the COI gene that are corroborated by morphology constitute species, whereas many of these species are polymorphic in colour pattern. Lectotypes are designated for 15 taxa in order to reduce uncertainty in the identity and application of the names. We provide new morphological keys and distribution maps for the species. Then we use four genes (fast-evolving mitochondrial COI and 16S; and slower nuclear PEPCK and opsin) to obtain an absolute chronogram of phylogenetic relationships among the species. From published estimates that the most recent common ancestor of the subgenus Mendacibombus diverged from the other bumblebees at the beginning of the Oligocene, our results support the crown group of Mendacibombus as having diversified in the late Miocene, events that both appear to have been associated with periods of climate cooling. Relative conservatism in the alpine/subalpine climate niche of Mendacibombus, as compared with the much more diversified climate niches in the sister group of all other bumblebees, may have contributed to constraining the number of Mendacibombus species to just one twentieth of the total number of extant bumblebee species.